Freudian dictionary a comprehensive guide to Freudian concepts - Valls, José Luis 1941- (Routledge, 2019)
The Freudian Dictionary provides a comprehensive and accessible guide to essential Freudian terms and concepts. Organized conceptually, the book is grounded in detailed and meticulous readings, and covers the full range of Freud's writings and subjects. It also provides an overview of the development, vicissitudes, and syntheses of Freud's unique lines of thought. Contemporary developments in psychoanalytic thought have aspired to surpass their Freudian origins. But this comprehensive guide to Freud's work provides a touchstone for those wishing to clarify these roots, and the foundations of the discipline itself. It will be a valuable companion to psychoanalysts in practice and training across a range of schools, as well as a reference work for sociologists, artists, philosophers, historians and other scholars
Description based on online resource; title from digital title page (viewed on June 10, 2019)
Keywords: Freud, Sigmund / 1856-1939; Psychoanalysis / Dictionaries